Defusing tensions in the South China Sea - Desker, Barry (2013)
As East Asia and Southeast Asia enter a more unpredictable period arising from growing territorial disputes, ther is a critical need for mutual restraint on the part of all disputing parties lest the tentions get out of hand. At the same time, there are lessons to be learnt.